PELATIHAN PEMASARAN ONLINE DENGAN MEMANFAATKAN MARKETPLACE BERSAMA PELAKU UMKM RT. 05 RW.07 PANDEGILING, SURABAYA - Novianto Eko Nugroho; Pontjo Bambang Mahargiono; Krido Eko Cahyono; Okto Aditya Suryawirawan (Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of the implementation of Community Service activities through Online Marketing Counseling and Marketplace Utilization for MSMEs residents of RT. 05 RW.07 Pandegiling, Surabaya to add insight into online marketing and marketplaces for MSME players in RT. 05 RW.07 Pandegiling, Surabaya. In addition to Lecturers and Students from the School of Economics Indonesia Surabaya as the activity implementation team, this counseling was also carried out by involving partners, namely Community Field Staff from PT Shopee International Indonesia. The result of this activity is an increased understanding of online marketing and marketplaces for MSME players in RT. 05 RW.07 Pandegiling, Surabaya Keywords: Online Marketing, Marketplace, MSME